Evaluating feeding as unconditioned stimulus for conditioning of an endocrine effect in Nile tilapia - Barreto, Rodrigo Egydio [UNESP]; Volpato, Gilson Luiz [UNESP] (Elsevier B.V., 2007)
This study tested the adequacy of feeding as an unconditioned stimulus (US) to condition an endocrine response (plasma cortisol increase) in the cichlid fish Nile tilapia (Oreochromis niloticus). In a first study, conditioning was confirmed in grouped fish in the only experiment using single-held Nile tilapia. In this test a conditioned stimulus (CS - aeration off) was associated with a stressor (air emersion for 2 min - US). We then assessed whether several events of paired CS-US resulted in a conditioned endocrine response (CR), in this case an increase in plasma cortisol after presentation of the CS only. Before testing feeding as US, the postprandial or social holding condition for feeding effects on cortisol levels was tested. Nile tilapia showed increased cortisol after feeding associated to social context (grouped fish), but not to food only (single-held fish). In a third study, feeding was tested as US in an experiment similar to the first study but an increase in feeding-induced cortisol could not be conditioned. The absence of CR suggests that the stressor affects acquisition of this response, which may be a consequence of stimulus intensity or biological relevance. This study expands the recently reported Pavlovian conditioning paradigm for endocrine response in fish. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: stress; cortisol; hypoxia; food competition; Pavlovian conditioning; feeding